Targeting transglutaminase 2 : pathways to celiac disease therapies - Endrizzi, Alexandra; Grunst, Pauline; Rudloff, Silvia; De Laffolie, Jan; Zimmer, Klaus-Peter; Stricker, Sebastian; Justus Liebig University Giessen (My University, 2025)
Background: Transglutaminase 2 (TG2)-mediated enzymatic modification of gliadin peptides plays a major role in the pathogenesis of celiac disease (CD). Different inhibitory mechanisms have been reported to reduce TG2 activity but comparative data on the cellular level are lacking. Furthermore, recent evidence suggested that endogenous redox proteins such as endoplasmic reticulum resident protein 57 (ERp57, inhibits TG2) and thioredoxin-1 (TRX, activates TG2) may regulate TG2 activity. In this study, we aimed to compare the effects and applicability of different inhibitors on the activity of recombinant and cellular TG2. Furthermore, we investigated the role of ERp57 and TRX in the context of CD by using siRNA-mediated knockdown in Caco-2 cells. Methods: The effect of TG2 inhibitors on recombinant and extracellular TG2 activity was investigated by using photometric and fluorometric quantitation of the cross-linking of biotinylated gliadin peptide P56-88 or 5-(biotinamido)-pentylamine. After siRNA knock-down, the protein levels of ERp57, TRX, and TG2 as well as TG2 activity were investigated by using Western blotting and fluorometry in Caco-2 cells. Results: The active-site-directed inhibitors ERW1041, KCC009, and cysteamine as well as the allosteric inhibitor LDN27219 revealed the most prominent reduction in recombinant and cellular (35%–50%) TG2 activity. In contrast, PX12, S-Nitroso-N-acetyl-DL-penicillamine, zinc chloride, and ascorbic acid either did not affect TG2 activity or had only moderate effects at high doses close to cytotoxic concentrations. SiRNA knockdown of TG2 resulted in a prominent reduction (63%) in TG2 activity, whereas knockdown of ERp57 did not; knockdown of TRX only slightly (27%) reduced TG2 activity. Conclusion: Active-site-directed inhibitors, LDN27219 and knockdown of TG2 expression significantly reduced extracellular TG2 activity and represent potential alternative treatment targets in the context of CD
Keywords: ddc:610